The Description of Parents' Knowledge in Modifying Food Ingredients in Efforts to Prevent Stunting in Children in the Tugusari Agricultural Area - Antonio Rudolfo; Ira Rahmawati; Peni Perdani Julianingrum (KHD-Production, 2022)
Stunting is one of the health problems, especially problems in the growth process that occurs in children caused by several causative factors including maternal factors, infant factors, economic factors, socio-cultural factors, and so on. The high incidence of nutritional diseases, especially stunting, is closely related to the level of nutrient intake given to children, especially in the first thousand days of life. The adverse effects that can be caused by nutritional problems in the toddler period in the long term are such as disruption of the brain, intelligence, physical growth disorders, and metabolic disorders in the body so that it can increase the risk of children experiencing lagging behind other children both physically and cognitively. The purpose of this study was to determine the description of parents' knowledge in modifying food ingredients in an effort to prevent stunting in children. In this study, the design used was descriptive observational. The population in this study were parents who had children under five (6-24 months) in the agricultural area of ​​Tugusari Village with a total of 67 mothers of toddlers. The sampling technique used by researchers was to use non-probability sampling techniques, namely purposive sampling with a total sample obtained of 57 respondents. Then for data collection techniques carried out through distributing questionnaires to respondents directly. The results of this study are the knowledge of parents in modifying food ingredients in an effort to prevent stunting in the Tugusari agricultural area in the moderate category, because the highest percentage of respondents' knowledge level is in the moderate knowledge category with a total of 38 people (66.7%), while the number of respondents with good knowledge category is 13 people (22.8%), and respondents with poor knowledge category have the least percentage value, totaling 6 people (10.5%). The conclusion of this study is that the majority of parents or research respondents already know enough about food modifications, especially complementary foods that will be given by mothers to each of their children in an effort to prevent stunting. Stunting is one of the health problems, especially problems in the growth process that occurs in children caused by several causative factors including maternal factors, infant factors, economic factors, socio-cultural factors, and so on. The high incidence of nutritional diseases, especially stunting, is closely related to the level of nutrient intake given to children, especially in the first thousand days of life. The adverse effects that can be caused by nutritional problems in the toddler period in the long term are such as disruption of the brain, intelligence, physical growth disorders, and metabolic disorders in the body so that it can increase the risk of children experiencing lagging behind other children both physically and cognitively. The purpose of this study was to determine the description of parents' knowledge in modifying food ingredients in an effort to prevent stunting in children. In this study, the design used was descriptive observational. The population in this study were parents who had children under five (6-24 months) in the agricultural area of ​​Tugusari Village with a total of 67 mothers of toddlers. The sampling technique used by researchers was to use non-probability sampling techniques, namely purposive sampling with a total sample obtained of 57 respondents. Then for data collection techniques carried out through distributing questionnaires to respondents directly. The results of this study are the knowledge of parents in modifying food ingredients in an effort to prevent stunting in the Tugusari agricultural area in the moderate category, because the highest percentage of respondents' knowledge level is in the moderate knowledge category with a total of 38 people (66.7%), while the number of respondents with good knowledge category is 13 people (22.8%), and respondents with poor knowledge category have the least percentage value, totaling 6 people (10.5%). The conclusion of this study is that the majority of parents or research respondents already know enough about food modifications, especially complementary foods that will be given by mothers to each of their children in an effort to prevent stunting.